PENGARUH KEBIJAKAN DIVIDEN, PERTUMBUHAN PERUSAHAAN, DAN PROFITABILITAS TERHADAP HARGA SAHAM (Studi empiris pada perusahaan LQ45 yang terdaftar di BEI tahun 2015-2019) - Layn, Yuyun Yuniarti; Latumahina, Shavira (Jurnal Akuntansi, 2022)
This study aims to test the effect of dividend policy, company growth, and profitability on the share price of LQ45 companies listed on the Indonesia Stock Exchange from 2016 to 2019. The population of this study is the LQ45 Index which was listed on the Indonesia Stock Exchange from 2016 to 2019. The sampling technique used was purposive sampling, and research data were obtained by 26 companies with four observation periods so that there were 104 samples. The data analysis method used is multiple linear regression. The results showed that the Dividend Policy, Company Growth, and Profitability significantly influence the stock price. In part, the Dividend Policy significantly affects the stock price, while the Company's Growth and Profitability have no significant effect on the share price